Characterization of bla AFM-1-positive carbapenem-resistant strains isolated in Guangzhou, China - Yingcheng Qin; Yuan Peng; Xiaonv Duan; Zhenli Song; Rong Huang; Yongyu Rui (BMC, 2023)
Abstract Background Carbapenemase-producing makes a great contribution to carbapenem resistance in Gram-negative bacilli. Bla AFM-1 gene was first discovered by us in Alcaligenes faecalis AN70 strain isolated in Guangzhou of China and, was submitted to NCBI on 16 November 2018. Methods Antimicrobial susceptibility testing was performed by broth microdilution assay using BD Phoenix 100. The phylogenetic tree of AFM and other B1 metallo-β-lactamases was visualized by MEGA7.0. Whole-genome sequencing technology was used to sequence carbapenem-resistant strains including the bla AFM-1 gene. Cloning and expressing of bla AFM-1 were designed to verify the function of AFM-1 to hydrolyze carbapenems and common β-lactamase substrates. Carba NP and Etest experiments were conducted to evaluate the activity of carbapenemase. Homology modeling was applied to predict the spatial structure of AFM-1. A conjugation assay was performed to test the ability of horizontal transfer of AFM-1 enzyme. The genetic context of bla AFM-1 was performed by Blast alignment. Results Alcaligenes faecalis strain AN70, Comamonas testosteroni strain NFYY023, Bordetella trematum strain E202, and Stenotrophomonas maltophilia strain NCTC10498 were identified as carrying the bla AFM-1 gene. All of these four strains were carbapenem-resistant strains. Phylogenetic analysis revealed that AFM-1 shares little nucleotide and amino acid identity with other class B carbapenemases (the highest identity (86%) with NDM-1 at the amino acid sequence level). The spatial structure of the AFM-1 enzyme was predicted to be αβ/βα sandwich structure, with two zinc atoms at its active site structure. Cloning and expressing of bla AFM-1 verified AFM-1 could hydrolyze carbapenems and common β-lactamase substrates. Carba NP test presented that the AFM-1 enzyme possesses carbapenemase activity. The successful transfer of pAN70-1(plasmid of AN70) to E.coli J53 suggested that the bla AFM-1 gene could be disseminated by the plasmid. The genetic context of bla AFM indicated that the downstream of the bla AFM gene was always adjacent to trpF and ble MBL. Comparative genome analysis revealed that bla AFM appeared to have been mobilized by an ISCR27-related mediated event. Conclusions The bla AFM-1 gene is derived from chromosome and plasmid, and the bla AFM-1 gene derived from the pAN70-1 plasmid can transfer carbapenem resistance to susceptible strains through horizontal transfer. Several bla AFM-1 -positive species have been isolated from feces in Guangzhou, China.